2020
DOI: 10.24059/olj.v24i1.1976
|View full text |Cite
|
Sign up to set email alerts
|

Student Preferences for Learning Resources on a Land-based Postgraduate Online Degree Programme

Abstract: Creating engaging online resources is an important part of the rapidly changing discipline of e-tutoring. There is increasing use of a wide range of media for online training but only a limited number of studies assessing their effectiveness. This study involved an educator working collegiately with cohorts of online students studying a specialist land-based postgraduate degree programme (n = 79).  The opinions of these mature online students, on current and potential learning resources, informed two intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Prior experience with Moodle may have also contributed to the high correlation between motivation and e-teaching materials and eassessments. This argument is supported by other researchers (Yili & Tsai, 2017;Slater & Davies, 2020;Cundell & Sheepy, 2018). The low correlation between motivation variables and e-discussion and e-grade checking and feedback could be attributed to the absence of real-time interaction between students and faculty in the way e-discussion and e-grade checking and feedback are implemented.…”
Section: Discussionsupporting
confidence: 55%
“…Prior experience with Moodle may have also contributed to the high correlation between motivation and e-teaching materials and eassessments. This argument is supported by other researchers (Yili & Tsai, 2017;Slater & Davies, 2020;Cundell & Sheepy, 2018). The low correlation between motivation variables and e-discussion and e-grade checking and feedback could be attributed to the absence of real-time interaction between students and faculty in the way e-discussion and e-grade checking and feedback are implemented.…”
Section: Discussionsupporting
confidence: 55%
“…Engaged learners are reported to have increased cognitive and metacognitive involvement in academic tasks, increased performance and productivity and higher achievement rates (Krause & Coates, 2008;Kuh, 2009;Slater & Davies, 2020). However, studies also state that establishing and maintaining academic engagement can be challenging (Reyes-Fournier, et al, 2020;Martin, Stamper, & Flowers, 2020).…”
Section: Attention Vs Distraction In E-learning Engagementmentioning
confidence: 99%
“…While more than 80% of the universities in the United States offer online courses (Parker, Lenhart, & Moore, 2011), the rate of offering online courses for other countries can go up to 50% in Asia, Africa, and the Middle East (Qayyum & Zawacki-Richter, 2019). The popularity of recent elearning programs stems from their interactive, repetitive, flexible, and customizable nature (Allen & Seaman, 2006;Arkorful & Abaidoo, 2015;Costley & Lange, 2018;Darling-Hammond et al, 2019;Ku & Chang, 2011;Lekawael, 2017;Slater & Davies, 2020;Waschull, 2001). This form of learning has been reported to provide various benefits for the new generation such as expanding access to more learning materials and sources (Hill, 2002;Hofmann, 2002;Li, 2007;Means et al, 2009); providing more affordable education opportunities for the learners that enhance active engagement (Katz & Yablon, 2002;Li, 2007); leading to higher achievement (Katz & Yablon, 2002;Rourke, 2001;Schrum, 2000); and maximizing the learning opportunities among several web-based tools, computer programs, MOOCs, or social media applications and platforms such as Facebook, Twitter, and Instagram (Abney et al, 2018;Aydin, 2012;Chawinga, 2017;Faizi et al, 2013;Fox & Bird, 2017;Wong et al, 2017;Xing, 2019).…”
mentioning
confidence: 99%
“…Slater and Davies [23] indicated that students prefer lectures, course notes, and primary literature available online, because these eteaching materials were perceived as available and easy to engage with from outside the university campus.…”
Section: Review Of Related Literaturementioning
confidence: 99%